Analysis of Brand Experience, Brand Satisfaction and Brand Trust Relationship to Brand Attachment - Deni Wardani; Reza Rekayasa Gustia (Indonesia Banking School, 2016)
In this modern age, people are required to have a high social mobility. The increasing number of private cars is resulted from the growing number of middle class in Indonesia. The main focus of this study was to analyze the effect of brand experience, brand satisfaction, brand trust towards brand attachment. this research is classified as descriptive analysis method to take samples and questionnaire as the main tool. The sample was 150 BMW users, especially those who have a BMW car in Jakarta. Respondents were selected using non probability sampling techniques and sampling convince. The results of analysis using structural equation model (SEM) found evidence for following relationships: brand experience significant positive effect on brand satisfaction, but it is not significant on brand trust. It has also found that brand satisfaction has significant positive effect on brand trust and brand attachment. However, brand satisfaction is found not having significant positive effect on brand attachment.